Placenta Percreta with Massive Hematuria - Zulfiqar, Yefri (Universitas Andalas, 2024)
Placenta accreta spectrum disorder (PAS) is diagnosed clinically when the placenta cannot be separated from the uterus after delivery. Abnormal placentas can be classified into three different entities such as placenta accreta, increta, and percreta. Placenta percreta is rare. Bladder bleeding due to placenta percreta has a poor prognosis. The main peculiarities of our case were a history of previous cesarean section, uterine curettage for miscarriage, and multiparity. Hematuria occurred in only 5% of patients. Early detection and appropriate treatment can save the patient's life